Analysis of the Role of Intimacy-Based Communication Therapy Intervention on Emotional Abuse in Betrayed Women Seeking Relationship Improvement with Their Spouse - Beytollahi , Fatemeh; Sadeghifard , Maryam (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to analyze the role of intimacy-based communication therapy intervention on emotional abuse in betrayed women who seek to improve their relationship with their spouse. Methods: This study employed a quasi-experimental design with a pre-test and post-test, including a control group. The study sample consisted of 30 women experiencing marital difficulties due to spousal infidelity, who were selected through convenience sampling from among women referring to counseling centers in Qeshm County. Participants were randomly assigned to two groups of 15 (15 participants in the control group and 15 in the experimental group). The sampling method involved identifying women with marital problems who reported experiencing spousal infidelity. The researcher then assessed their willingness to participate in educational sessions before selecting the final sample. The experimental group underwent an intimacy-based communication therapy intervention, which was conducted in eight 90-minute sessions, held twice a week. Data collection was carried out using the Emotional Abuse Questionnaire developed by Brehimi (2008). The data were analyzed using SPSS software, employing both descriptive statistics (demographic tables and charts) and inferential statistics (covariance analysis). Findings: The findings indicated that intimacy-based communication therapy intervention had a significant effect on emotional abuse and all its dimensions—except for social restriction—among betrayed women seeking to improve their relationship with their spouse. Conclusion: Therefore, intimacy-based communication therapy intervention can be effectively utilized for supporting women and girls who have experienced emotional distress.